Probiotics in the Complex Treatment of Various Diseases of the Gastrointestinal Tract - K. V. Ivashkin; M. S. Reshetova; O. Yu. Zolnikova; V. R. Korneev; E. N. Shirokova (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2020)
Aim. To present up-to-date information on the role of microbiota and its disorders in the development of various diseases of the gastrointestinal tract (GIT), including functional diseases, as well as to consider current methods of correction and maintenance of normal microbiota.General findings. The human microbiome affects many organs at the biochemical, molecular and genetic levels. It has been confirmed that the microbiome participates in the development of inflammatory and functional diseases of the gastrointestinal tract, affects the immune system, central nervous system and mental status. An important problem of everyday medical practice consists in the management of patients with functional disorders of the gastrointestinal tract. The “7 × 7” questionnaire created in 2014 by a group of specialists from I.M. Sechenov First Moscow State Medical University in collaboration with Valenta Pharm allows dynamic evaluation of the clinical course of functional gastrointestinal diseases. The most frequent functional gastrointestinal disorder – irritable bowel syndrome (IBS) – is characterized by a quantitative and qualitative change in the intestinal microflora, which, together with inflammatory changes in the intestinal wall, may act as a trigger for the onset of symptoms, as well as lead to a functional change in the receptor apparatus of pain pathways. Over thelast decade, the number of studies on the use of probiotics for the treatment of various gastrointestinal diseases has increased significantly. The pathogenetic effect of the change in the normal ratio of microorganisms in the intestine proves the inclusion of probiotics in the complex treatment of functional disorders of the gastrointestinal tract to be reasonable.Conclusion. Improved methods for assessing the microbiome state allows evaluation of the composition of the human intestine microflora in various diseases, thus facilitating the search for new approaches to correcting and maintaining the normal ratio of microorganisms for managing patients with various gastrointestinal diseases.